Issuance of a Search Warrant for Narcotics Crime in Indonesia - Sahuri Lasmadi (LAW REFORM, 2020)
Concerning narcotics crime in Indonesia in addition to the Police Investigator, the National Narcotics Agency (BNN) also has the authority to conduct investigations and investigations. Search is part of the investigation process, but is often constrained by a search warrant. The research method used is a normative legal research method. This method uses a statutory approach and a conceptual approach. This research puts forward secondary data in the form of binding legal material such as Law Number 35 of 2009 concerning Narcotics (Narcotics Law), books and other legal research journals. The results of this study indicate Article 81 of the Narcotics Law states that Police Investigators and BNN investigators are authorized to conduct investigations of the abuse and illicit trafficking of Narcotics and Narcotics Precursors. One of them is that an ordinary search or normal search can be carried out by the investigator after first obtaining permission from the head of the District Court, then searching under extraordinary and urgent circumstances, ie the investigator can search without first obtaining permission from the head of the local District Court, however after a search the investigator must immediately seek the approval of the head of the District Court.